Mensurarão do desempenho escolar I. Procedimento não convencional para aplicação de provas objetivas - Piza, Ivan Giacomo; Bruschi, Luis; Ribeiro, Roseli (Semina: Ciências Exatas e Tecnológicas, 2004)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> A non conventional objective method of examination applied for both theoretical and practical knowledge, is presented It was developped in order to attempt the conditions concerning to a great number of students. Reliability and usability viewpoints are mainly analysed and particular advantage is attributed to the preparation and application steps that are made easier and more economic.